PERSEPSI MAHASISWA FAKULTAS KEDOKTERAN UPN VETERAN JAKARTA TERHADAP PILIHAN MATA KULIAH ELEKTIF DAN HUBUNGANNYA DENGAN RENCANA KARIR MASA DEPAN - Hany Reina Natasya, (2022)
Introductuion: The National Standard for Medical Professional Education adds elective course items into the curriculum in order to produce skilled doctors to keep pace with changes in the era of globalization. Elective courses are expected to accommodate and help direct students by providing information that can assist students in planning further studies so that students can be more focused in choosing a career to develop themselves. Methodology: This study used a quantitative method with a cross-sectional design on 187 medical students in their 1st, 2nd, and 3rd year using total sampling technique. The research instrument in the form of a questionnaire was distributed using a google form. Data analysis was carried out by using the Contingency Coefficient test. Results: On the results of the univariate test, it was found that most of the respondents had positive perceptions of elective courses, chose elective courses in Hospital Management, Health Law, Interprofessional Relationship and Research Management And Entrepreneurship and career plans as specialist/ clinicians. Bivariate analysis with the contingency coefficient test resulted in a P value of 0.101. Discussion: The result might be affected by other factors, one of them being the current elective course options do not match students' interests. Conclusion: It can be concluded that there is no relationship between the choice of elective courses and the future career plans of the students of the Faculty of Medicine, UPN Veterans Jakarta.